2023
DOI: 10.1093/plphys/kiad385
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors TgbHLH95 and TgbZIP44 cotarget terpene biosynthesis geneTgGPPSinTorreya grandisnuts

Abstract: Terpenes are volatile compounds responsible for aroma and the postharvest quality of commercially important xiangfei (Torreya grandis) nuts, and there is interest in understanding the regulation of their biosynthesis. Here, a transcriptomics analysis of xiangfei nuts after harvest identified 156 genes associated with the terpenoid metabolic pathway. A geranyl diphosphate (GPP) synthase (TgGPPS) involved in production of the monoterpene precursor GPP was targeted for functional characterization, and its transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The results revealed that aroma compounds were mainly classified into seven major groups, including terpenes, alcohols, aldehydes, esters, oxygenated terpenes, alkanes, and ketones, with terpenes being the most abundant, accounting for 85.19–93.90% in ‘Xi Fei’ ( Figure 2 A) and 67.75–93.24% in ‘Xiangya Fei’ ( Figure 2 B), suggesting that terpenes are the main aroma-presenting substances during the postharvest ripening process of T. grandis . We previously explored changes in the aroma composition of ‘Xi Fei’ at 20 °C and a 90% RH environment during postharvest ripening, revealing that terpenes accounted for 56–87%, and that the terpene content increased significantly on days 4 and 8 [ 36 ]. Our current results showed that the total terpene content in both cvs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that aroma compounds were mainly classified into seven major groups, including terpenes, alcohols, aldehydes, esters, oxygenated terpenes, alkanes, and ketones, with terpenes being the most abundant, accounting for 85.19–93.90% in ‘Xi Fei’ ( Figure 2 A) and 67.75–93.24% in ‘Xiangya Fei’ ( Figure 2 B), suggesting that terpenes are the main aroma-presenting substances during the postharvest ripening process of T. grandis . We previously explored changes in the aroma composition of ‘Xi Fei’ at 20 °C and a 90% RH environment during postharvest ripening, revealing that terpenes accounted for 56–87%, and that the terpene content increased significantly on days 4 and 8 [ 36 ]. Our current results showed that the total terpene content in both cvs.…”
Section: Resultsmentioning
confidence: 99%
“…The screened nuts were mixed, divided into three groups each of 5 kg, and then placed at 25 ± 2 °C and in a 90% RH ± 2% RH environment for postharvest ripening treatment [ 35 ]. Generally, the postharvest ripening process of Torreya grandis nuts usually takes a period of 10–15 days under appropriate temperature and humidity conditions [ 36 ]. Therefore, the nuts were then sampled on days 0, 5, 10, 15, and 20.…”
Section: Methodsmentioning
confidence: 99%
“…Collection of the seeds occurred monthly from May to September. Subsequently, the seeds were carefully de-scaled using a manual peeling method based on established protocols for T. grandis seed kernels [ 26 , 27 , 28 ], ensuring clean and intact seeds, then rapidly frozen in liquid nitrogen and preserved at −80 °C for subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…To induce transient overexpression in pear leaves, the full-length PbrGA2ox1 gene without the stop codon was amplified using the primer pair PbrGA2ox1 -EGFP-F/R (Table S5 in Additional File 2 ) and framed into the p1300-EGFP vector digested at XbaI and BamHI sites to generate overexpression fusion constructs PbrGA2ox1 _OE with upstream CaMV 35S promoter, termed as 35S: PbrGA2ox1 in our previous work [ 30 ]. Then, the PbrGA2ox1 _OE fusion vector was transformed into the Agrobacterium tumefaciens GV3101-pSoup cells via thermal stimulation .…”
Section: Methodsmentioning
confidence: 99%
“…Previously, RNA-seq helped to reveal the fundamental determinants that contribute to interstock-induced dwarfism in sweet persimmon [ 26 ], and altitude-dependent potato tuber coloring [ 27 ]. Moreover, RNA-seq has also been widely utilized to derive novel insights into the functions of several genes, such as the SlWRKY35 -activated carotenoid biosynthesis in tomatoes [ 28 ], MdMYB94 -induced ester biosynthesis in apples [ 29 ], and TgbHLH95- and TgbZIP44 -targeted terpene biosynthesis in ‘xiang fei’ ( Torreya grandis ) nuts [ 30 ]. Thus, RNA-seq can help efficiently explore the potential mechanisms underlying phenotypic alterations arising from gain-of-function or loss-of-function of genes.…”
Section: Introductionmentioning
confidence: 99%